Hormonal control of vas deferens fluid volume and aquaporin expression in rats - Ramli, Nur Siti Khadijah; Giribabu, Nelli; Karim, Kamarulzaman; Salleh, Naguib (Springer, 2019)
Precise regulation of vas deferens fluid volume which is important for sperm survival might be influenced by testosterone. In order to investigate changes in vas deferens fluid volume and aquoporins (AQP) isoforms expression under testosterone influence, orchidectomized Sprague–Dawley rats were given 125 and 250 µg/kg/day testosterone with or without flutamide, an androgen receptor blocker or finasteride, a 5alpha-reductase inhibitor for seven consecutive days. Following treatment completion, vas deferens was perfused and changes in the fluid secretion rate and osmolality were determined in the presence of acetazolamide. Rats were then sacrificed and vas deferens was harvested for histology, tissue expression and distribution analyses of AQP-1, AQP-2, AQP-5, AQP-7 and AQP-9 proteins by Western blotting and immunohistochemistry, respectively. Our findings indicate that testosterone causes vas deferens fluid secretion rate to increase, which was antagonized by acetazolamide. Fluid osmolality increased following testosterone treatment and further increased when acetazolamide was given. Co-administration of flutamide or finasteride with testosterone causing both fluid secretion rate and osmolality to decrease. Histology revealed increased size of vas deferens lumen with increased thickness of vas deferens stroma. Expression of AQP-1, AQP-2 and AQP-9 were detected in vas deferens but not AQP-5 and AQP-7, and the levels of these proteins were increased by testosterone treatment mainly at the apical membrane of vas deferens epithelium. In conclusion, increased in vas deferens fluid secretion rate under testosterone influence mediated via the up-regulation of AQP-1, 2 and 9 might be important for vas deferens fluid homeostasis in order to ensure normal male fertility. © 2018, Springer Nature B.V.